(untitled) (Czech Journal of International Relations, 2023)
The present book offers a deeply probing view into the development of 20th-century leadership. Against the background of six prominent statesmen, it unfolds each figure’s abilities and strategic reasoning. The book focuses explicitly on Konrad Adenauer, Charles de Gaulle, Richard Nixon, Anwar Sadat, Lee Kuan Yew, and Margaret Thatcher as case studies with an ever-lasting impact on international affairs.